2017
DOI: 10.1097/gox.0000000000001481
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Long Thoracic Nerve Decompression and Neurolysis Versus Muscle and Tendon Transfer Operative Treatments of Winging Scapula

Abstract: Background:Injury to long thoracic and the spinal accessory nerves can cause winging scapula as a result of weakness and paralysis of the trapezius and serratus anterior muscles. Although these nerve and muscle operations have been reported to correct winging scapula due to various causes, there is no report on comparing the outcomes of these procedures in peer-reviewed Pubmed-indexed literature. In this article, we compared the improvements in the restoration of shoulder functions in winging scapula patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“… 17 A meta-analysis of our published results of decompression and neurolysis versus the reported outcomes of muscle or tendon transfer procedures shows that these procedures are comparatively effective in the restoration of shoulder functions in winging scapula patients in comparison with muscle or tendon transfer operations. 18 Other investigators have also shown excellent to good clinical outcomes over 2 years of nerve decompression and neurolysis in both the upper and lower extremities. 22 , 23 Klifto and Dellon have shown success in relieving pain in the long-term (over 2 years) follow-up of nerve decompression and neurolysis in leprous and diabetic patients.…”
Section: Discussionmentioning
confidence: 95%
“… 17 A meta-analysis of our published results of decompression and neurolysis versus the reported outcomes of muscle or tendon transfer procedures shows that these procedures are comparatively effective in the restoration of shoulder functions in winging scapula patients in comparison with muscle or tendon transfer operations. 18 Other investigators have also shown excellent to good clinical outcomes over 2 years of nerve decompression and neurolysis in both the upper and lower extremities. 22 , 23 Klifto and Dellon have shown success in relieving pain in the long-term (over 2 years) follow-up of nerve decompression and neurolysis in leprous and diabetic patients.…”
Section: Discussionmentioning
confidence: 95%